Immune response to stress induced by conticosteroid in common carp ( cyprinus carpio linnaeus) exposed to aeromonas hydrophila - Lumanlan, Susan C.
The effect of simulated stress induced by Cortisol implantation in common carp (Cyprinus carpio) was studied. Humoral mediated responses to injected antigens following Cortisol treatment were assessed by using the passive haemolytic plaque technique and indirect haemagglutination assay. A single Cortisol implant and subsequent challenge to Aeromonas hydrophila elicited modulation in the fish immune system and also histopathological changes in the kidney, spleen and thymus. Hyperglycaemia which is a stress related physiological change was associatively manifested.